Evaluation of Illuminance Measurement Data through Integrated Automated Blinds and LED Dimming Controls in a Full-Scale Mock-Up - Chul-Ho Kim; Kwang-Ho Lee; Kang-Soo Kim (Energies, 2020)
In this study, the indoor illuminance of a full-scale mock-up with LED system and external automated blinds was quantitatively evaluated by performing experiments involving integrated blinds and LED dimming controls. Actual illuminance experimental data were constructed and analyzed using commercialized blind control logic. The results revealed changes in the LED dimming ratio (turning-off ratio), and that the indoor illuminance required for the indoor space of 500 ± 30 lx could be secured in all cases when daylight was introduced according to weather conditions. It was found that because the angle and vertical position (VP) were fixed, manual blind controls could not efficiently use daylight, even though they could cut off solar radiation. When the blinds were automatically controlled in three-steps based on the exterior vertical illuminance under clear sky, the dimming rates of Zones A and B were found to be 68 and 50%, respectively. When the blinds were automatically controlled in four-steps, the dimming rates of Zone A (1.5 m from the window) and Zone B (4.5 m from the window) were found to be at 70% and 52%, respectively. If the VP and slat angle could be adjusted without lowering all the blinds, it would be possible to secure work plane illuminance, because the inflow of daylight increases, without the direct impact of direct sunlight and glare. These results indicate that integrated blinds and LED dimming controls can contribute to maintaining standard illuminance and saving lighting energy using daylight.